Evaluating the Capacity of Standard Investment Appraisal Methods - Mehari Mekonnen Akalu (Tinbergen Institute, 2002)
The survey findings indicate the existence of gap between theory and practice of capital budgeting. Standard appraisal methods have shown a wider project value discrepancy, which is beyond and above the contingency limit. In addition, the research has found the growing trend in the use of value management models. The presence of correlation between the frequency of monitoring and project value discrepancy, and the absence of uniformity in the use of evaluation methods throughout the life span of a project are among the results of the study.
Keywords: G30; G31; L6; L8; L9; M10; O22; O32; 330; Capital Budgeting; Investment Appraisal; DCF Methods; Project Analysis; Shareholder Value Analysis; Value Management Techniques.; Cash Flow; Betriebliche Budgetierung; Wertanalyse; Theorie